(untitled) (Journal of Misan Researches, 2024)
Lady Sakina bint Al-Hussein (peace be upon them) between truth and fabrication in the historical novel "The Forgotten Princesses." by Jamal explores the historical account of Lady Sakina bint Al-Hussein (peace be upon them) and Aisha bint Talha. The novel, published in its first edition in 2011, lacks authentic content, especially regarding the biography of the wise Lady Sakina bint Al-Hussein (peace be upon them). The book lacks reliable sources untainted by political turmoil, biases, and personal opinions. It often presents embellished narratives that appeal to weak minds and uninformed individuals. Those who lack knowledge and enlightenment tend to follow such narratives and behaviors. There is a temporal and environmental gap between the author and the subjects, with the latter witnessing the degradation of heavenly values and Islamic teachings, while the former praises and admires such values. Psychological factors also play a role, as some individuals see themselves in places of shame and dissolution rather than places of asceticism and solitude. The study aims to refute the statements, positions, and regrets filled within the novel and offers alternative perspectives.